Isıl püskürtme teknikleriyle plastik ve plastik esaslı kompozit tozlarla kaplanmış yüzeylerin mekanik ve kimyasal özelliklerinin incelenmesi - Öksüz, Mustafa (My University, 1999)
Plastik ve plastik esaslı kompozit malzemeler yüksek korozyon direnci, yüksek darbe dayanımı, elektrik yalıtkanlığı, düşük yoğunlukları gibi üstün özellikleri nedeniyle değişik endüstriyel amaçlarla yaygın olarak kullanılmaktadırlar. Metallerin yüzeyine kaplanarak gerçekleştirilen plastik toz kaplamalar üstün özelliklerinden faydalanmak mümkündür. Plastik kaplamaların yaygın olarak kullanıldığı alanlardan biri düşük sıcaklıklarda bile tokluk özelliklerini koruyabilmesi, korozyona ve atmosferik şartlara karşı dayanıklı olmaları kullanım amaçları arasındadır. Isıl püskürtme teknikler (alevle püskürtme, plazma püskürtme) yaygın olarak kullanılan tekniklerdendir. Bu yöntemler ile plastik tozların kaplanması işlemi son yıllarda uygulamaya konulan alternatif bir yüzey koruma işlemidir. Alevle ve plazma püskürtme yöntemlerinde en çok kullanılan termoplastik türleri arasında naylon, polipropilen (PP), poli(vinilklorür) (PVC), polietilen (PE), poli(tetrafloraetilen) (PTFE), cam takviyeli ve takviyesiz naylon, termoset esaslı reçineler ve bunların kopolimerleridir. Alevle ve plazma püskürtme yöntemleri ile plastik ve plastik esaslı kompozit tozlarla yapılan kaplamalar korozyon, ve atmosferik şartlara dayanıklılığa sahiptir. Bir çok püskürtme yönteminde olduğu gibi plastik kaplama işleminde de sarf malzemesi toz formunda olup, kullanım amacına bağlı olarak çeşitli özelliklere sahip farklı karışımlardan oluşmuş değişlik tipte tozlar kullanılmaktadır. Isıl püskürtme parametrelerinin esnek ve geniş bir spektrumdaki malzeme ve bileşenlerinin kullanımına izin vermesi bu yöntemi çok kullanılan bir yöntem durumuna getirmiştir. Bu araştırmada alevle ve plazma ile püskürtme tekniklerinde değişik bileşimdeki metal ve alaşımları laboratuar ve endüstriyel şartlarda farklı bileşimlerdeki plastik tozlarla kaplanacaktır. Bu teknikler kullanılarak EVOH ve alüminyum-silisyum esaslı polyester plastik kaplamaların bağ mukavemeti, aşınma, makrosertlik değerleri ile kimyasallara ve atmosferik şartlara karşı dayanıklılıkları belirlendi. Kaplamalara etki eden püskürtme parametrelerinin değiştirilerek (püskürtme mesafesi, kaplama kalınlığı vs.) çeşitli tipte yapılan kaplamaların bağ mukavemetler çekme deneyi, aşınma mukavemetleri pin-on-disk ve ball-on disk yöntemleri ile yapılacak olup aşınma yöntemin esası aşınma sonucu kaplamanın ağırlık kaybına dayandırıldı. Plastik kaplamaların ışık ve tarama elektron mikroskop (SEM) yöntemleriyle mikroyapı ve mikro analiz (E.D.S.) ve Infrared Spektofotometre incelemeleri yapılarak değerlendirilmeler yapıldı. The main characteristics of the powder coatings are; ease of processing, safety in handling and processing, absence of gas or odour pollution during the coating, high impact resistance even at low service temperatures, chemical resistance to acids and alkalis, excellent weather resistance, suitability to be used in food and drink sectors, ease in repair when it is damage. Coating powders are also used for decoration and protection purposes. Powder coatings are applied in anumber of ways such as dip coating, electrostatic coating, flame spray coating, plasma spray coating etc,. In a spray process, powders of the same particle size and distribution are sprayed onto different surfaces. The substrates are generally heated above the melting point of plastic powder resin or good adhesion may not be obtained. The substrate materials usually are cleaned by sand or grit blasting to form an anchor pattern that improves adhesion of flame sprayed powder coating. An obvious disadvantage of a spraying process is the presence of an open flame. Spray operators must be highly skilled and specially trained. Plastic powder coating may be subdivided into two main classes i.e; thermosets and thermoplastics. Thermosets powder materials are composed of oligomer that are designed to react when heated in the presence of a catalyst. This results in an irreversible transformation processing. Thermoplastic however, is a reversible process. Plastic powders that have a crystalline structure are stronger than the powders which have amorph structures. Mainly used plastics powders are nylon, polypropylene (PP), polyethylene (PE), polytetrafloraethylene (PTFE), polyvinlyclorur (PVC) and reinforced powders and their copolymers. Plastic powder and plastic based composite powders are used in specific applications such as electrical insulation, corrosion protection, abrasion resistance, friction and wear resistance etc,. In a powder coating, the properties of the coating are strongly dependent on the chemical composition and the flame spraying parameters. The main parameters are the flame types and spraying distance. This study deals with chemical resistance, bond strength properties, wear properties and the morphology of the flame and plasma sprayed ethylene vinyl alcohol copolymer and aluminium silicon polyester powder coatings. Bond strength, wear resistance, resistance to chemicals and morphology of the coating surfaces were studied. EVOH and aluminium silicon polyester composite powders were employed as coating materials and flame and plasma spray were investigated. Aluminium silicon polyester coating performed with and without NiAl intermediate bond layer. Tensile tests were performed according to ASTM C - 633 and pin-on-disk/ ball-on-disk wear tests performed according to ASTM G 99 90 and 91. Microstructure/ morphology, wear and fracture surfaces of the coatings were examined by using light and Scanning Electron Microscopy (SEM). A micro analysis was also performed. Moreover an attempt has been made to establish a correlation between process parameters, mechanical properties and microstructure of the coating. In chapter one and two; general introdution of the coating systems and the treatment of the coating surfaces are outlined. In chapter three, the coating powders and spraying techniques are described. In chapter four, the materials used and the experiments performed are explained. In chapter five six the results and discussion of the coating studies are given. In chapter six, the conclusions are presented.
Keywords: Kimya mühendisliği ve ilgili konular; Metalürji; PLASTİK TOZLAR